Correlation of Reproduction Management on Losses of Dairy Farmers in Wagir District, Malang Regency - Ishaq, Rizal Maulana; Suharsono, Suharsono; Harijani, Nenny; Hidanah, Sri; Mustofa, Imam (Universitas Airlangga, 2021)
This study was conducted to find out how much losses the breeders get when their cattle experience a decline in day open (DO), service per conception (S/C), and calving interval (CI).There were 108 lactating dairy cows from the dairy farm, Wagir District, Malang Regency.The data that has been taken is then processed by analysis using linear regression method.The results of the analysis prove that reproductive management has an effect of 82% on farmer expenditure.For each setback DO per day, the farmer pays Rp. 609,05.Meanwhile, for each additional S/C the farmer pays Rp. 99,921.7.For each setback the farmer CI will incur a fee of IDR 228,54 / day.So that the equation found is expendses = 609,05 (DO) + 99,921.7 (s / c) +228,54 (CI).